Theoretical and experimental evaluation of detached endcaps for 3 T birdcage coils. - Alecci, M; Collins, C; Wilson, J; Liu, W; Smith, M; Jezzard, P (2003)
The use of detached endcaps for 3 T birdcage coils was investigated both theoretically and experimentally. Finite difference time domain analysis, along with workbench and MRI techniques, were used to map the radiofrequency (RF) B(1) distribution along the coil axis with and without an endcap. Without an endcap the measured B(1) value at the service end of the birdcage was only 45% of the value at the coil's center. This was improved to 85% with a detached endcap of maximum achievable diameter (375 mm), positioned 4 mm from the RF shield. The B(1) field distribution on the patient side of the coil was unaffected by the presence of the endcap. The dependence of the B(1) distribution as a function of endcap diameter was also investigated. Surprisingly, simulations and experiments show that there is an optimum ratio of endcap-to-birdcage coil diameter (approximately 1.08) that gives the best B(1) homogeneity. In the human head the optimized endcap, positioned 16 mm from the RF shield, improves the MRI signal amplitude from 55% to 85% of maximum toward the service end. This novel endcap design is easy to implement with existing birdcage coils, and could prove useful when flexibility in access to the RF coil is required.